Mec1 and Tel1: an arresting dance of resection. (22nd January 2014) - Beyer, Tracey; Weinert, Ted
<x xml:space="preserve">Abstract</x> At sites of damage DNA is resected to enable the optimal form of repair, directed by homology. But how does the cell regulate resection while coordinating with the cell cycle? In this issue of The EMBO Journal, Clerici et al define missing links between DNA resection and cell cycle arrest during repair, showing that Mec1 can inhibit resection to subsequently activate arrest by Tel1.